2016
DOI: 10.1111/jmi.12386
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic time‐lapse visualization of surface pore filtration on particulate matter trapping process

Abstract: A scanning electron microscope (SEM) was used to dynamically visualize the particulate matter (PM) trapping process on diesel particulate filter (DPF) walls at a micro scale as 'time-lapse' images corresponding to the increase in pressure drop simultaneously measured through the DPF. This visualization and pressure drop measurement led to the conclusion that the PM trapping in surface pores was driven by PM bridging and stacking at constricted areas in porous channels. This caused a drastic increase in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Figure 10 shows the increase in the pressure drop for each superficial velocity. In the case of 34.5 mm/s, similarly to the case of the soot-trapping process in the previous work (1) , we observe three phases of the increase in the pressure drop: caused by the bridging-structure formation, the deposition of nanoparticles in surface pores, and the growth of the cake layer. With decreasing velocity, the increase in the pressure drop due to the deposition in surface pores became smaller.…”
Section: Effect Of Superficial Velocity On Pressure Dropsupporting
confidence: 80%
See 2 more Smart Citations
“…Figure 10 shows the increase in the pressure drop for each superficial velocity. In the case of 34.5 mm/s, similarly to the case of the soot-trapping process in the previous work (1) , we observe three phases of the increase in the pressure drop: caused by the bridging-structure formation, the deposition of nanoparticles in surface pores, and the growth of the cake layer. With decreasing velocity, the increase in the pressure drop due to the deposition in surface pores became smaller.…”
Section: Effect Of Superficial Velocity On Pressure Dropsupporting
confidence: 80%
“…Recently, the mechanism of the increase in the pressure drop with respect to soot loading was revealed (1) (Figure 1). At the beginning of soot deposition, the soot is trapped on the surface of grains, which are the elements of the DPF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, it was put into DPF holder, made of stainless steel, and ceramic paste was used to seal around DPF sample and holder. In order to visualize the cross-sectional vertical wall of the DPF, the horizontal top wall was removed (8,9) . The top surfaces of the vertical walls and the holder were polished simultaneously and uniformly utilizing abrasive papers with grit sizes ranging from As a result, the PM included ash with a weight ratio of 11 wt.%.…”
Section: Scanning Transmission Electron Microscopy (Stem)mentioning
confidence: 99%
“…The recent study [2] has revealed the pressure drop increasing phenomenon due to the soot accumulation on the particulate filter.…”
Section: Introductionmentioning
confidence: 99%